"Hold Me Tight": The Generalizability of an Attachment-Based Group Intervention to Chinese Canadian Couples. Issue 1 (2nd January 2018) - Wong, Tat-Ying; Greenman, Paul S.; Beaudoin, Valérie
ABSTRACT: "Hold Me Tight" (HMT) groups are an adaptation of emotionally focused therapy (EFT) for couples and have emerged out of 30 years of research into the efficacy and process of EFT. The goal of this study was to test the effects of a Chinese-language version of the HMT relationship enrichment program in a sample of Chinese Canadians. Twenty-three men and 23 women (N = 46) in committed couple relationships completed an HMT relationship education program with their partners in Toronto, Ontario, Canada. Results indicated statistically significant improvements in participants' satisfaction with their attachment relationships, in their attachment security, and in their family functioning. The implications of these findings are discussed in light of relevant cross-cultural literature on attachment and couple relationships.